The Impact of Social Media on the Efficiency of Online Business Performance - Nguyen, Tran Hung; Le, Hoang Anh; Cu, Le Xuan; Hang, Vu Thi Thuy (Indian Journal of Finance, 2022)
This study aimed to develop some criteria to assess the impact of social media on the online business activities of Vietnamese enterprises. As the country’s e-commerce has been experiencing phenomenal growth, to assess the impact of social media on the same, we designed a questionnaire to assess five criteria based on relevant studies and collected data from 356 respondents in the positions of Head and Deputy of sales, marketing, and customer services departments of 80 typical and small and medium e-commerce enterprises. The results showed that Vietnamese enterprises did not know how to use the loyal customer community to influence potential customers on social networks and leverage the intelligence and creativity of customers for business operations. In addition, most Vietnamese enterprises spent a large sum of money on social networking activities but had low interaction because they often used too much text and very little visual content. To the best of our knowledge, this is the first study that attempted to identify the criteria for assessing the impact of social media on the online businesses of Vietnamese enterprises. Emphasizing that social networks have become an important channel for the business of Vietnamese enterprises, the study provides researchers and enterprises with a broader and deeper understanding of how social media can be better utilized to create a positive impact in promoting online business activity.